Role of sugarcane straw allelochemicals in the growth suppression of arrowleaf sida - Sampietro, Diego Alejandro (2007)
Previous studies suggested that allelochemicals from sugarcane straw may suppress the growth of arrowleaf sida (Sida rhombifolia L.). A study was conducted to establish: (1) the direct or indirect role of the organic molecules from sugarcane straw leachate on the growth suppression of arrowleaf sida and (2) if leachate phytotoxins induce proline accumulation in arrowleaf sida tissues as an adaptative response to a water or an oxidative stress. Inhibition of root elongation was the primary effect of sugarcane straw leachate on arrowleaf sida grown in unsterile soil. Addition of activated charcoal to unsterile soil before incorporation of straw leachate reduced the inhibition in root growth suggesting a direct participation of organic molecules in leachate phytotoxicity on arrowleaf sida. Inorganic straw constituents did not inhibit root growth while microbial activity increased leachate phytotoxicity. Soil chemical analysis suggested a direct action of organic molecules in leachate phytotoxicity rather than variations in macro and micronutrients or nutrient microbial immobilization. Straw leachate induced proline accumulation in roots and cotyledons of arrowleaf sida. Proline increase was related with oxidative stress in the roots but not in the cotyledons. Our results indicate a direct action of organic compounds from sugarcane straw and/or their microbial transformation products on root growth of arrowleaf sida. These substances induced proline accumulation in roots mainly as consequence of an oxidative stress while water stress may be the main cause of high proline content in the cotyledons. Although the observed responses could be due to phenolic compounds, the involvement of organic molecules with other chemical nature could not be excluded.